Intake of kidney bean (phaseolus vulgaris) extract as postpartum blues management - Desta Ayu Cahya Rosyida; Nina Nikmah; Khoiriyah Noviastuti (Health Science Journal of Indonesia, 2021)
Background: Postpartum blues is common in postpartum Mother with more prone to crying, more anxious, often unstable and more emotional than usual. Zinc supplementation is one of the methods needed for postpartum blues conditions. Kidney bean (phaseolus vulgaris) extract has the highest zinc content. This study aimed to examine the effect of intake kidney bean extract (phaseolus vulgaris) as a zinc source as management mother with Postpartum Blues Methods: Quantitative study with an experimental study design (Quasi Experiment Design) with a Pre and Post-test Control Group Design. The instrument used to measure the mood of a mother after childbirth was EPDS (Edinburgh Post-Partum Depression Scale). The total sample was 68 mothers who experienced postpartum blues in Ngerandu Ponorogo primary health care. The Mann-Whitney was used to analyse and find out the difference in mood improvement before and after the intervention in the experimental group and the control group. Results: The results showed that there was a statistically significant difference in mood levels of mothers with postpartum blues before and after intervention (p value of 0.001 (<0.005). This result indicated that intake of kidney bean (Phaseolus vulgaris) extract had an effect on the mood level of mothers with postpartum blue. Conclusion: Intake of kidney bean (phaseolus vulgaris) extract on the incidence of postpartum blues possibly improvement mood in the experimental group after the treatment for 1 month. Keywords: kidney bean (phaseolus vulgaris) extract, postpartum blues, postpartum mother Abstrak Latar belakang: Postpartum blues umum terjadi pada ibu postpartum dengan tanda sering menangis, khawatir yang berlebihan, emosional yang tidak stabil. Suplementasi zinc merupakan salah satu metode yang dibutuhkan untuk kondisi postpartum blues. Ektrak kacang merah (phaseolus vulgaris) memiliki sumber nutrisi zinc yang tinggi, Penelitian ini bertujuan untuk menguji efek konsumsi ekstrak kacang merah (phaseolus vulgaris) sebagai sumber zinc sebagai manajemen ibu dengan postpartum blues Metode: Penelitian kuantitatif dengan design Quasi Experiment pre dan post control grup. Instrumen pengukur mood ibu setelah melahirkan adalah EPDS (Edinburgh Post-Partum Depression Scale). Total Sampel 68 ibu yang mengalami postpartum blues di Puskesmas Ngerandu Ponorogo. Analisis statistik menggunakan Mann-Whitney untuk menemukan perbedaan perubahan mood ibu postpartum blues sebelum dan sesudah dilakukan intervensi pada grup intervensi dan kontrol. Hasil: Hasil menunjukkan bahwa terdapat perbedaan signifikan tingkat mood ibu dengan postpartum blues sebelum dan sesudah dilakukan intervensi (p : 0,001 (<0,005). Hasil mengindikasikan bahwa konsumsi ekstrak kacang merah (phaseolus vulgaris) memiliki efek pada tingkat mood ibu yang sedang mengalami postpartum blues. Kesimpulan: Konsumsi ekstrak kacang merah (phaseolus vulgaris) pada ibu postpartum blues memungkinkan untuk perubahan mood pada grup intervensi setelah diberikan treatment selama 1 bulan. Kata kunci: ekstrak kacang merah (phaseolus vulgaris), postpartum blues, ibu postpartum